Exploring the Histone Acetylation Cycle in the Protozoan Model Tetrahymena thermophila - Wahab, Suzanne; Saettone, Alejandro; Nabeel-Shah, Syed; Dannah, Nora; Fillingham, Jeffrey (Frontiers in Cell and Developmental Biology, 2020)
The eukaryotic histone acetylation cycle is composed of three classes of proteins, histone acetyltransferases (HATs) that add acetyl groups to lysine amino acids, bromodomain (BRD) containing proteins that recognize acetyl-lysine and effect downstream function, and histone deacetylases (HDACs) that catalyze the reverse reaction. Dysfunction of selected proteins of these three classes is associated with human disease such as cancer. Additionally, the HATs, BRDs and HDACs of fungi and parasitic protozoa present potential drug targets. Despite their importance, the function and mechanisms of HATs, BRDs, and HDACs and how they relate to chromatin remodeling remain incompletely understood. Tetrahymena thermophila (Tt) provides a highly tractable single-celled free-living protozoan model for studying histone acetylation, featuring a massively acetylated somatic genome, a property that was exploited in the identification of the first HAT Gcn5 in the 1990s. Since then, Tetrahymena remains a mostly unexplored model for the molecular analysis of HATs, BRDs, and HDACs. Studies of HATs, BRDs and HDACs in Tetrahymena have the potential to reveal the function of HATs and BRDs relevant to both fundamental eukaryotic biology and to the study of disease mechanisms in parasitic protozoa.